Analisis Proses Manufaktur pada Mesin Pencacah Ban Multifungsi Berpenggerak Motor Listrik - Roihan, Andy Akbar; Irawan, Hery (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2025)
The amount of waste from used tires in Indonesia continues to grow each year. Since used tires are challenging to decompose, various efforts are being made to repurpose and reduce this waste. One such solution involves using a tire shredder machine, which breaks down tires into smaller pieces, making them easier to recycle or use as raw materials in various industries. This machine helps mitigate the environmental impact of used tires by preventing them from accumulation. The components for developing this machine are readily available, and it features a user-friendly system that is easy to operate. The manufacturing process of the tire shredder machine involves several steps: material and tool preparation, measurement, cutting, welding, turning, drilling, and time management. Once assembled, the production cost (HPP) and production time are calculated. A test run is then performed to ensure the machine achieves the desired shred size. The machine frame is constructed from hollow steel (50 x 50 x 2 mm). Based on the calculations, the production cost (HPP) amounts to IDR 19,882,976.31, with a total production time of 225.86 seconds.